Comparing everolimus‐based immunosuppression with reduction or withdrawal of calcineurin inhibitor reduction from 6 months after heart transplantation: The randomized MANDELA study. Issue 11 (5th April 2019) - Barten, Markus J.; Hirt, Stephan W.; Garbade, Jens; Bara, Christoph; Doesch, Andreas O.; Knosalla, Christoph; Grinninger, Carola; Stypmann, Jörg; Sieder, Christian; Lehmkuhl, Hans B.; Porstner, Martina; Schulz, Uwe
Abstract : In the 12‐month, open‐label MANDELA study, patients were randomized at month 6 after heart transplantation to (1) convert to calcineurin inhibitor (CNI)‐free immunosuppression with everolimus (EVR), mycophenolic acid and steroids (CNI‐free, n = 71), or to (2) continue reduced‐exposure CNI, with EVR and steroids (EVR/redCNI, n = 74). Tacrolimus was administered in 48.8% of EVR/redCNI patients and 52.6% of CNI‐free patients at randomization. Both strategies improved and stabilized renal function based on the primary endpoint (estimated GFR at month 18 posttransplant postrandomization) with superiority of the CNI‐free group vs EVR/redCNI: mean 64.1 mL/min/1.73 m 2 vs 52.9 mL/min/1.73 m 2 ; difference + 11.3 mL/min/1.73 m 2 ( P < .001). By month 18, estimated GFR had increased by ≥ 10 mL/min/1.73 m 2 in 31.8% and 55.2% of EVR/redCNI and CNI‐free patients, respectively, and by ≥ 25 mL/min/1.73 m 2 in 4.5% and 20.9%. Rates of biopsy‐proven acute rejection (BPAR) were 6.8% and 21.1%; all cases were without hemodynamic compromise. BPAR was less frequent with EVR/redCNI vs the CNI‐free regimen ( P = .015); 6 of 15 episodes in CNI‐free patients occurred with EVR concentration < 5 ng/mL. Rates of adverse events and associated discontinuations were comparable. EVR/redCNI from month 6 achieved stable renal function with infrequent BPAR. One‐year renal function can be improved by early conversion to EVR‐based CNI‐free therapy but requires close EVR monitoring. Clinical trials registry : ClinicalTrials.gov NCT00862979. Abstract : The 12‐month, randomized, open‐label MANDELA study shows that switching patients at 6 months after heart transplantation from standard immunosuppression to everolimus, mycophenolic acid, and steroids or to reduced‐exposure calcineurin inhibitor, everolimus, and steroids improves renal function in either case, but the enhanced renal benefit seen in the calcineurin inhibitor–free group requires close monitoring of everolimus exposure to avoid an increased risk of biopsy‐proven acute rejection. Tsay and Eisen comment in their editorial on page 2967 .